Effects of recurrence on the cognitive performance of patients with bipolar I disorder: implications for relapse prevention and treatment adherence (2010)
ABSTRACT: bjective: To determine if the repeated occurrence of manic episodes in bipolar I disorder (BD-I) patients is associated with reduced cognitive performance, which could in turn imply a worsening in the disorders evolution. Method: Cognitive performance in euthymic patients was assessed using attention, memory, and executive function tests on 24 BD-I patients who had experienced only 1 manic episode, on 27 BD-I patients with 2 manic episodes, on 47 BD-I patients with 3 or more manic episodes, and on 66 healthy control subjects. Results: In BD-I patients, number of manic episodes was positively associated with poorer performance on neurocognitive tests, an association that was not accounted for by depression, disease chronicity, onset, or medication. Significant differences in attention and executive function were found between patients and controls and in those patients who had had just 1 manic episode compared to those who had 3 or more. Conclusion: The number of manic episodes predicted poor cognitive performance, suggesting that the recurrence of mania may have a longterm neuropsychological impact. Prospective follow-up studies need to be completed to explore this effect further as better treatment adherence may have a protective effect on neurocognitive function.